O discurso sobre a arte de fazer discursos e o ensino moderno de oratória - Ivan Capdeville Junior (2013)
This study aims to look at the antique ideals that drove the formation process of the speakers and remain echoing in pedagogical practices for the development of oral and textual production, to assess their relevance and effectiveness in contemporary times. It is based on the contrast between the speech of those who produce instructions for the development of rhetorical skills and the speech of those who want to improve themselves in this area. It wants to find the first of these discursive formations from the analysis of prescriptions found in manuals of rhetoric, written throughout history. The second, from initial diagnoses and final evaluations of students in a modern course on oratory. It resumes fundamental concepts of the classical world and, inserted into the line of Rhetorical Pedagogy , argues that Rhetoric offers concepts, paths and fully applicable solutions to the challenge of improving the teaching and learning of languages. Finally, it proposes Rhetorical Development Theory to explain the functioning of activities aimed at teaching public speaking and to serve as a guide to those who want to dedicate themselves to the growth in oratory.